Noise exposures of firefighters during training activities - Root, Kyle, author; Brazile, William, advisor; Sandfort, Delvin, committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2011)
Occupational hearing loss is the most common work-related injury in the United States according to the National Institute for Occupational Safety and Health (NIOSH). Consequently, NIOSH recommends that occupational noise exposure be among the top occupational hazard research areas of the next century. Firefighters represent a unique population in which noise exposure data are difficult to obtain. The unique settings in which firefighters perform their duties (e.g., inside burning structures) make it difficult to collect noise exposure data and quantify exposures due to environmental factors and unpredictability. Furthermore, firefighting requires that multiple tasks by each participant be accomplished during emergency responses. In order to address the challenge of obtaining personal noise samples from firefighters during emergency situations, this study was conducted to gather firefighter personal noise samples during training exercises that simulated on-scene firefighting tasks. Noise exposure data were collected on five training days during the summers of 2010 and 2011. Two training exercises were executed each day, totaling ten training exercises. Each training exercise averaged 35 minutes in duration and included ten to eleven participants, resulting in ninety-three total personal noise exposure samples. Noise monitoring results showed that none of the ninety-three (100%) firefighter samples were exposed to noise exceeding the Occupation Safety and Health Administration (OSHA) permissible exposure limit (PEL) of an 8-hour time-weighted average (TWA) of 90 dBA. Nine of ninety-three (9.6%) exposures were above the OSHA action level (AL) of 50% dose when extrapolated across an 8-hour workday. Additional analysis was performed after dividing the noise exposure data into three groups consisting of Interior, Exterior, and Engineering categories. This division showed a statistically significant difference (alpha = 0.1) between the interior and engineer categories in relation to noise exposure.
Keywords: exposure; training; noise; firefighters